2017
DOI: 10.1159/000464464
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Effectiveness of Bis-Chloroethylnitrosourea Wafer Chemotherapy in Elderly Patients with Recurrent Glioblastoma

Abstract: Objective: To assess the safety and effectiveness of bis-chloroethylnitrosourea (BCNU) wafers in elderly patients with recurrent glioblastoma (GBM). Methods: Patients with recurrent GBM operated on between 2007 and 2014 were divided into 3 groups: >65 years with BCNU wafer implantation, >65 years without BCNU wafer implantation, and ≤65 years with BCNU wafer implantation. We compared survival and complications. Results: A total of 79 patients were identified: 24 in the older BCNU group (median age 68.2 years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Acquired resistance to the previous standard of care for GBM, bis-chloroethylnitrosourea (BCNU), leads to an increased sensitivity to TMZ 14 . Because BCNU can still be a component of second-line treatment for GBM 15 18 , we tested whether our TMZres cells exhibited altered responsiveness to BCNU. Since the resistant cell lines are populations selected from the wild type cell lines they have a more reproducible phenotype as the variability or heterogeneity of the cell line has decreased.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acquired resistance to the previous standard of care for GBM, bis-chloroethylnitrosourea (BCNU), leads to an increased sensitivity to TMZ 14 . Because BCNU can still be a component of second-line treatment for GBM 15 18 , we tested whether our TMZres cells exhibited altered responsiveness to BCNU. Since the resistant cell lines are populations selected from the wild type cell lines they have a more reproducible phenotype as the variability or heterogeneity of the cell line has decreased.…”
Section: Resultsmentioning
confidence: 99%
“…For decades BCNU was the standard of care for GBM, and it is still a component of some second-line regimens. Findings from clinical studies examining the efficacy of BCNU in recurrent GBM post-TMZ treatment are inconsistent, with some suggesting BCNU remains active while others demonstrate no benefit 16 18 . These TMZres cell line pairs may therefore also prove to be valuable resources for defining contexts in which BCNU is or is not appropriate second-line treatment, and for identifying other, more appropriate therapies for TMZ-resistant GBM.…”
Section: Discussionmentioning
confidence: 99%
“…There were 8 studies eligible which examined the use of systemic or in situ nitrosureas for the treatment of pGBM eligible and were included in this analysis. Table 2 summarizes the 8 studies [17][18][19][20][21][22][23][24] that examined the use systemic or in situ nitrosoureas for the treatment of pGBM. These studies provided Class III evidence.…”
Section: Q1-synthesismentioning
confidence: 99%
“…The authors concluded that the regimen was not bene cial. Klein et al [19] retrospectively reviewed a cohort of 79 patients with recurrent GBM and methylated MGMT promoter.…”
Section: Other Nitrosoureasmentioning
confidence: 99%
“…Recently, Klein et al . retrospectively analyzed outcomes in three different group of patients with recurrent GBM [ 46 ]. Median survival after progression was 9.2 months in elderly patients (>65 years) receiving BCNU wafers, 7.6 months in elderly patients not receiving BCNU wafers (p = 0.34), and 9.2 months in younger patients receiving BCNU wafers (p = 0.35).…”
Section: Background and Rationalementioning
confidence: 99%